Evaluación no lineal de dos postes diferentes (2012)
ABSTRACT: Endodontically treated teeth that will be restored with crowns and which have lost part of their dental structure need a cast post or a prefabricated post to improve final restoration retention and therefore to be able to regain their functionality and aesthetics. The literature suggests when to use a cast or prefabricated post, but it is not conclusive in terms of which one has a better stress distribution, which post material or shape is better, or whether their modulus of elasticity is related to load distribution along the tooth’s axis. Methods: by using Solid Works, two models of a maxillary central incisor with all its supporting structures were made, one with a cast post and another one with a prefabricated post plus an all-ceramic crown. By means of finite element analysis both teeth were subjected to loads of 200, 400, 600 and 800 N up to reaching their plasticity. Results: at 200 and 400 N, both posts showed different stress distribution patterns without altering the restoration or the tooth’s root. Conclusions: at normal masticatory loads, both posts are likely to restore a tooth that needs addition of a post.